PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BERBASIS ETNOMATEMATIKA PADA KERATON YOGYAKARTA - Zainnur Wijayanto (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2017)
This type of research is research development with model development of 4-D modification of Thiagarajan, which includes three phases, definition, design and development. This research was conducted in class VIII SMP Taman Dewasa Ibu Pawiyatan Yogyakarta with class VIIIA as experimental class and class VIIIB as control class. Data analysis techniques to assess the validity of the media with content and construct validation performed by 3 experts. The practicality of the media is assessed using a student response questionnaire and an observation sheet on the learning implementation. The effectiveness of learning is assessed by media testing in the experimental class by analyzing the learning outcomes using one sample t-test and the proportion for the learning test result, with the independent t-test to compare the learning outcomes in the experimental and control classes. The validation results on the learning media state that the media is valid by expert with an average of 4.53. From the test results obtained (1) practicality: from the observation of the implementation of learning categorized very well, with an average of 4.14. The response of learners > 75% responded well. (2) Effectiveness: from the analysis of trial results, the achievement of the completeness of problem solving ability in classical manner with the mean value > 75 exceeds 75%, and the result of t-test shows the average ability in the experimental class is greater than the control class average. So that obtained mathematical learning media based on ethnomatematics that valid, practical and effective.Keywords : Ethnomatematics, Keraton Yogyakarta, Learning Media